MEDU-32. IN-VIVO REPROGRAMMING OF POSTMITOTIC NEURONS INDUCES MEDULLOBLASTOMA - Aiello, Giuseppe (Neuro Oncol, 2019)
In the last years significant progress has been made to identify the cells of origin of many cancers and the majority of data points towards stem cells and progenitors. Notably, it is common opinion that these cells should possess a proliferative capacity, therefore postmitotic neurons have not been considered as suitable cell of origin of human and mouse cancer. Indeed, the transition of neural progenitor to differentiated postmitotic neurons is thought to be irreversible in physiological and pathological conditions. Here we show that neurons reprograming may occur upon oncogenes activation and it leads to brain cancer formation in vivo. Using a conditional Cre-recombination system we manage to recapitulate human cancer model in mice ad to demonstrate that the postmigratory mature granule neurons (MGNs) can be reprogrammed in-vivo. Interestingly, MGNs seem to possess defined characteristic that allow the reprogramming and the cancer formation, since activation of oncogenic pathways leads to cancer formation only in specific area of brain. For the first time we demonstrate the chance to reprogram postmitotic neurons into cancer cells shedding new light on the mechanisms of cancer formation. Postmitotic cells of other tissues may also possess tumor initianting cell features and our findings can be considered as a starting point to a new field in cancer biology.